The Correlation Of Knowledge Levels With Behavior Of Using The Contraceptives Among The Fertile Couples - Karno Karno; Wahyuningsih Wahyuningsih; Dina Putri Utami L; Anafrin Yugistyowati; Abror Shodiq (Alma Ata University Press, 2020)
Unwanted pregnancy among the fertile couples which gives the negative impacts, can be prevented with efforts by using contraceptives to the fertile couples. But, the behavior of using contraceptives may vary among them. It might due to many factors, one of which is the knowledge levels of those fertile couples in using the contraceptives. This research is aimed at finding out the correlation between the knowledge levels with the behavior of using the contraceptives. The research employed the design of analytical observational study with cross-sectional approach. Penelitian ini dilakukan di Dusun Metes, Argorejo, Sedayu, Bantul. The respondents were selected by using techniques of sampling to 235 patients, dengan kriteria inklusi usia 15-49 tahun, masih memiliki pasangan. The researchers used questionnaires as research instruments and chi square as the analysis. The results showed that the behavior of using contraceptives could be divided into three kinds: the usage, the selection, and the substitution of the contraceptives.The chi-square analysis showed that the knowledge levels of the patients were not correlated to the behavior of using contraceptives either in the usage( p-value = 0,872 ), the selection ( p-value = 0,795), and the substitution( p-value = 0,872 ). Due to the result that there was no correlation between the level of knowledge and the behavior of using contraceptives among the fertile couples, this research argued that the more better the knowledge of the patients the more critical in view they decided to use the contraceptives. In this context, the role of health workers is necessarily needed to give counselings to those fertile couples in order to help them decide in doing it properly.